1967
DOI: 10.1161/01.res.21.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Alterations at the Alveolar Level in Pulmonary Edema

Abstract: The electron microscopic alterations of the alveolar septum in advanced hemodynamin and alloxan-induced pulmonary edema were compared. Pulmonary edema was produced in anesthetized dogs by means of increased lefy atrial pressure and hemodilution and by allocan administration. Sections of pulmonary tissue from these dogs and similarly anesthetized controls were processed for and examined by light and electron microscopy. In the hemodynamic form of edema the interstitial fluid collects only in the collagen-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
3
1

Year Published

1970
1970
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 19 publications
6
40
3
1
Order By: Relevance
“…In addition, the alveolar wall exhibited fissures perpendicular to its several layers, although the integrity of these layers was otherwise maintained ( Figure 5). These changes in pulmonary tissue structure completely differ from those reported by Cottrell et al [11] for other edema types (which were caused by alloxan or static hydraulic lung pressure). This discrepancy suggests that although pulmonary edemas might appear to have similar features, electron microscopic observation may yield very different findings, due to differences in pathogenesis.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In addition, the alveolar wall exhibited fissures perpendicular to its several layers, although the integrity of these layers was otherwise maintained ( Figure 5). These changes in pulmonary tissue structure completely differ from those reported by Cottrell et al [11] for other edema types (which were caused by alloxan or static hydraulic lung pressure). This discrepancy suggests that although pulmonary edemas might appear to have similar features, electron microscopic observation may yield very different findings, due to differences in pathogenesis.…”
Section: Discussioncontrasting
confidence: 90%
“…The present in vivo microscopic observations showed slower blood flow in capillaries of some areas used electron microscopic observation to investigate pulmonary edema induced by causes other than lung reexpansion. Cottrell et al [11] used electron microscopy to observe edema caused by static hydraulic lung pressure and reported that such edema only developed on alveolar walls in areas where collagen-fiber tissues were present (with no changes at the blood-air barrier). The same group analyzed electron microscopic images of alloxan-induced edema, which showed clasmatosis in the epithelium and endothelium but no edema in the alveolar septum [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial injury is evident as early as 0.5 hr after administration of xylazine and becomes more pronounced by 12 hr. These changes are similar to those caused by known edemagenic agents such as alloxan and a-naphthylthiourea, which cause increased permeability PE (11,12).…”
Section: Discussionsupporting
confidence: 65%
“…The increase in lymph flow in the Pseudomonas experiments was 10-fold or less and lymph-plasma globulin ratios tended to fall from base line. It has been suggested that for some increased permeability states, the diameter of the larger pores simply increases (26,38). As illustrated by Fig.…”
Section: Appendixmentioning
confidence: 93%